Modelling the cancer growth process by stochastic differential equations with the effect of chondroitin sulfate (cs) as anticancer therapeutics - Mazma Syahidatul Ayuni, Mazlan; Norhayati, Rosli; Nina Suhaity, Azmi; Solachuddin Jauhari, Arief Ichwan (IOP Publishing, 2017)
A stochastic model is introduced to describe the growth of cancer affected by anti-cancer therapeutics of Chondroitin Sulfate (CS). The parameters values of the stochastic model are estimated via maximum likelihood function. The numerical method of Euler-Maruyama will be employed to solve the model numerically. The efficiency of the stochastic model is measured by comparing the simulated result with the experimental data.